(iii) Musculoskeletal malignancy – non-surgical management. Issue 3 (June 2015) - Speed, Lesley; Esler, Claire
Abstract Primary musculoskeletal cancers are relatively rare and should be managed by specialist centres which can deliver multimodal, multi-professional treatment. Patients with localized primary bone or soft tissue sarcomas may be cured but prognosis has to be guarded due to high rates of local recurrence and many are not curable. To reduce patient suffering and maintain quality of life requires a multidisciplinary approach.